Common molecular pathways in amyotrophic lateral sclerosis and frontotemporal dementia: review - Weishaupt, Jochen H.; Hyman, Anthony A.; Đikić, Ivan (Trends in molecular medicine, 2016)
Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are age-related neurodegenerative diseases in which predominantly motor neurons and cerebral cortex neurons, respectively, are affected. Several novel ALS and FTD disease genes have been recently discovered, pointing toward a few overarching pathways in ALS/FTD pathogenesis. Nevertheless, a precise picture of how various cellular processes cause neuronal death, or how different routes leading to ALS and FTD are functionally connected is just emerging. Moreover, how the most recent milestone findings in the ALS/FTD field might lead to improved diagnosis and treatment is actively being explored. We highlight some of the most exciting recent topics in the field, which could potentially facilitate the identification of further links between the pathogenic ALS/FTD pathways related to autophagy, vesicle trafficking, and RNA metabolism.
Gesehen am 08.07.2021